Social-environmental-economic problems of chemical undustry of Russia within the process of globalization of world economy - S. M. Sukhorukova; P. V. Sukhorukov; M. S. Brykina (Тонкие химические технологии)
The transition of Russia to “opened economy” contributed to the development of national economy mostly oriented on export of raw materials as well as to reduction of science consuming branches of chemical industry. In order to change such situation the concept of “institutional” economy is proposed. This concept will permit to restore the diversified complex of science consuming branches of Russian economy on the new system basis and simultaneously to solve the respective environmental, social and economic problems of chemical industry.